(untitled) (Research, Society and Development, 2020)
Currently, grapevine plants in the Jaguari, located in the central-western region in Rio Grande do Sul state - Brazil, show symptoms of phytotoxicity, possibly resulting from the application of agrochemicals in agricultural production areas. The grape is a product of great economic, social and cultural value for the region. In this sense, Municipal Law nº 3,163 restricts the use of herbicides derived from chemical composition 2,4-D (dichlorophenoxyacetic) throughout the Jaguari territory from September 15 to March 15 of each agricultural year, independent of modality of its application. Therefore, the objective of this paper is to identify and quantify 2,4-D residues in the vine leaves by QuEChERS method and HPLC-MS / MS analysis. The samples were collected in six properties located within the perimeter delimited by Municipal Law nº 3,163. The sampling period was weekly from 09/29/2017 to 06/12/2017, making a total of 62 samples. The vines were collected and were stored in properly identified plastic bags and sent to the Laboratory of Analysis of Residues and Pesticides (LARP), at the Federal University of Santa Maria (UFSM). Problems of plant phytotoxicity were observed during the sampling period. It was verified the presence of residues of the herbicide in 69% of the samples, concluding that the drift of the product may be the cause of the damage to the vines pointed out by the Jaguari producers.